Experimental Transmission of Kaposi's Sarcoma–Associated Herpesvirus (Kshv/Hhv-8) to Scid-Hu Thy/Liv Mice - Dittmer, D. (The Rockefeller University Press, 1999)
Kaposi's sarcoma–associated herpesvirus (KSHV/HHV-8) is a novel human lymphotropic herpesvirus linked to several human neoplasms. To date, no animal model for infection by this virus has been described. We have examined the susceptibility of C.B-17 scid/scid mice implanted with human fetal thymus and liver grafts (SCID-hu Thy/Liv mice) to KSHV infection. KSHV virions were inoculated directly into the implants, and viral DNA and mRNA production was assayed using real-time quantitative polymerase chain reaction. This revealed a biphasic infection, with an early phase of lytic replication accompanied and followed by sustained latency. Ultraviolet irradiation of the inoculum abolished all DNA- and mRNA-derived signals, and infection was inhibited by ganciclovir. Viral gene expression was most abundant in CD19(+) B lymphocytes, suggesting that this model faithfully mimics the natural tropism of this virus. Short-term coinfection with HIV-1 did not alter the course of KSHV replication, nor did KSHV alter levels of HIV-1 p24 during the acute phase of the infection. Although no disease was evident in infected animals, SCID-hu Thy/Liv mice should allow the detailed study of KSHV tropism, latency, and drug susceptibility.